The STEM Enhancement in Earth Science “Mosquito Mappers” Virtual Internship: Outcomes of Place-Based Engagement with Citizen Science - Cho, Holly; Low, Russanne D.; Fischer, Heather A.; Storksdieck, Martin (Frontiers in Environmental Science, 2021)
In this paper, we describe a virtual high school earth science enhancement program that embeds a citizen science experience within a scientist-mentored research internship. We demonstrate the success of the program as measured by knowledge of pertinent science concepts and processes, and changes in future career orientation, and explore the role of place-based citizen science in interns’ experience of their research projects. The STEM Enhancement in Earth Science (SEES) Mosquito Mappers Virtual Internship connected high school interns with research opportunities applying NASA Earth Observations to the global health threat of mosquito-vector borne diseases. The interns engaged in 120–150 h of research working closely with NASA subject matter expert mentors, and making use of the GLOBE Observer citizen science infrastructure to collect and analyse data. In the virtual format, interns were able to participate in activities synchronously or asynchronously through an online learning platform, web conferencing software and social media. Students developed and completed either an independent or small team research project leveraging data collected using the place-based citizen science mobile application, GLOBE Observer. We found that participants were motivated by conducting fieldwork in and around their communities using the GLOBE Observer app. Local fieldwork enabled the student researchers to apply their prior knowledge of their natural and built landscapes, while also contributing to the reduction of mosquito-borne disease risk in their communities. This finding highlights the benefit of coupling citizen science to a virtual internship. Interns shared that their interest in research, and research in the earth sciences specifically, increased as a result of participating in the internship program. By leveraging citizen science data collection and reporting tools, existing data, and analysis tools, the program represented a robust, cost effective research experience conducted in a virtual environment, lowering barriers to participation and broadening access to STEM enhancement opportunities for all.